2000
DOI: 10.1002/1096-9896(2000)9999:9999<::aid-path645>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the differentiation and function of osteoclasts

Abstract: The osteoclast is the cell that resorbs bone. It has been known for many years that its formation and function are regulated by cells of the osteoblastic lineage. Recently the molecular basis for this regulation was identified; osteoblastic cells induce osteoclastic differentiation and resorptive activity through expression of tumour necrosis factor (TNF) activation-induced cytokine (TRANCE) (also known as RANKL, ODF, OPGL, and TNFSF11), a novel membrane-inserted member of the TNF superfamily. Osteoclastic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(75 citation statements)
references
References 134 publications
0
74
1
Order By: Relevance
“…It is very likely that these processes are separately regulated. However, although there have been considerable advances in our understanding of the mechanisms through which the differentiation of osteoclasts is regulated [1][2][3], much less is known of the mechanisms that modulate their function.…”
Section: Introductionmentioning
confidence: 53%
“…It is very likely that these processes are separately regulated. However, although there have been considerable advances in our understanding of the mechanisms through which the differentiation of osteoclasts is regulated [1][2][3], much less is known of the mechanisms that modulate their function.…”
Section: Introductionmentioning
confidence: 53%
“…Dynamic histomorphometric analysis clearly demonstrated that ovariectomized LysM.Rac1 KO samples had lower bone formation rates compared to WT, which is the expected consequence of decreased osteoclast activity [35,36] in the osteoclast-osteoblast coupling paradigm. We speculate that the reduced osteoclast activity in the LysM.…”
Section: Osteoporosis-induced Rac Knock-out Mouse Modelmentioning
confidence: 99%
“…RANKL is a critical factor inducing osteoclast differentiation. It is secreted by osteoblasts and its action on osteoclasts is antagonized by a soluble receptor called osteoprotegerin (OPG) [100,101]. Mice deficient for Rankl are severely osteopetrotic due to the lack of osteoclasts and the absence of bone resorption [102].…”
Section: Beta-adrenergic Signaling In Osteoblasts Increases Bone Resomentioning
confidence: 99%